(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract Fairy tales have long perpetuated a dualistic portrayal of morality, often relegating female characters to extreme archetypes of virtue or villainy. This paper explores the deconstruction of villainy in female characters within fairy tales, examining their complex motivations, sociocultural contexts, and modern reinterpretations. By revisiting tales like Snow White, Sleeping Beauty, and Cinderella, and analyzing their retellings, the study seeks to challenge traditional binaries and present a nuanced understanding of female agency. This inquiry underscores the importance of reevaluating these narratives to foster a more inclusive and dynamic literary discourse.